Nighttime Sleep, Daytime Napping, and Labor Outcomes in Healthy Pregnant Women in Taiwan. Issue 6 (31st October 2013) - Tsai, Shao‐Yu; Lin, Jou‐Wei; Kuo, Lu‐Ting; Lee, Chien‐Nan; Landis, Carol A.
Abstract We prospectively examined the associations of nighttime and daytime sleep during the third trimester of pregnancy with labor duration and risk of cesarean deliveries in a convenience sample of 120 nulliparous women who completed sleep‐related questionnaires and wore wrist actigraphs for up to 7 days. Nap duration and 24‐hour sleep duration were inversely associated with labor duration in women with vaginal delivery. Neither actigraphy‐derived nor self‐reported sleep variables were associated with type of delivery (e.g., vaginal, cesarean). Results showed a beneficial effect of sleep on labor duration and suggest that studies of sleep duration effects on labor and pregnancy outcomes require a consideration of the amount of both daytime and nighttime sleep. © 2013 Wiley Periodicals, Inc. Res Nurs Health 36: 612–622, 2013